INOVASI MEDIA PEMBELAJARAN GEOGRAFI INTERAKTIF BERBASIS ARCGIS STORY MAPS PADA MATERI MITIGASI DAN ADAPTASI KEBENCANAAN UNTUK SMA SAMARINDA - Nur Jannah, Putri; Nur Mawaddah, Najma; Vita Romadon Ningrum, Mei; Azmi, Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a web-based geography learning media using ArcGIS Story Maps on disaster mitigation and adaptation material for Grade XI high school students. The research used Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research conducted at SMA Negeri 14 Samarinda. Data collection instruments included interview sheets, observation sheets, validation questionnaires from media experts, as well as student response questionnaires. The result showed that: (1) The development stages of ArcGIS Story Maps learning media were carried out through five ADDIE stages. In the analysis stage, it was found that 61.8% of students stated the media used was not varied, 97.1% of students needed more attractive and innovative media, and 91.2% of students had never used ArcGIS Story Maps. (2) The feasibility test result showed that media expert validation obtained 96% (Very Feasible), material expert validation obtained 83% (Very Feasible), linguist expert validation obtained 88% (Very Feasible), and learning expert validation obtained 99% (Very Feasible), with an average score of 91.5% (Very Feasible). In addition, the student response questionnaire showed an average percentage 0f 91.5% (Very Feasible). ArcGIS Story Maps can serve as an innovative teaching tool in geography lessons.